Предмет: Математика,
автор: VladSanzhenakov2003
-3(2,1m-1)+4,8=-6,7m+9,4
Приложения:
Ответы
Автор ответа:
0
-3(2,1m-1)+4,8=-6,7m+9,4
-6,3m + 3 + 4,8 = -6,7m + 9,4
-6,3m + 7,8 = -6,7m + 9,4
6,7m - 6,3m = 9,4 - 7,8
0,4m = 1,6
m = 1,6 : 0,4
m = 4
-6,3m + 3 + 4,8 = -6,7m + 9,4
-6,3m + 7,8 = -6,7m + 9,4
6,7m - 6,3m = 9,4 - 7,8
0,4m = 1,6
m = 1,6 : 0,4
m = 4
Похожие вопросы
Предмет: История,
автор: aveasaanil
Предмет: Литература,
автор: russkiichel228
Предмет: Информатика,
автор: ghxychc
Предмет: Математика,
автор: Sasha108801
Предмет: Алгебра,
автор: FreemanKz